2021
DOI: 10.3892/ol.2021.12434
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycans and their modification as promising anticancer targets in hepatocellular carcinoma (Review)

Abstract: Hepatocellular carcinoma (HCC) is one of the most common types of primary liver cancer. Despite advancements in the treatment strategies of HCC, there is an urgent requirement to identify and develop novel therapeutic drugs that do not lead to resistance. These novel agents should have the potential to influence the primary mechanisms participating in the pathogenesis of HCC. Heparan sulfate proteoglycans (HSPGs) are major elements of the extracellular matrix that perform structural and signaling functions. HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Additionally, the distribution between brain parenchyma and brain capillaries of the three [I 125 ]scFvs were similar to another scFv8D3-containing BBB shuttle of similar size which has been previously studied 48 . One potential explanation for the lack of increased brain uptake of HS(+)scFv8D3 is that even though it might be unable to bind some HS patterns it might still be unable to the HS present at the BBB, due to the fact that HS patterns are heterogenous with varying tissue composition [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the distribution between brain parenchyma and brain capillaries of the three [I 125 ]scFvs were similar to another scFv8D3-containing BBB shuttle of similar size which has been previously studied 48 . One potential explanation for the lack of increased brain uptake of HS(+)scFv8D3 is that even though it might be unable to bind some HS patterns it might still be unable to the HS present at the BBB, due to the fact that HS patterns are heterogenous with varying tissue composition [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…HSPGs have a wide range of functions, including regulation of receptor trafficking, regulation of endocytosis and as a binding site for a wide range of ligands 25 27 . HSPGs wide range of functions are enabled by their HS chains 28 , which consist of long, unbranched negatively charged disaccharide repeats, varying in chain lengths and sulphation patterns 27 , 29 . Binding of proteins to the negatively charged HS require positively charged HS binding motifs 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…HSULF-1 is a tumor suppressor protein [ 17 ], whereas the role of HSULF-2 in pathophysiology remains partially known [ 18 ]. However, previous studies have shown that HSULF-2 is upregulated and promotes hepatic [ 17 , 19 , 20 ], renal [ 21 ], colorectal [ 22 ], pancreatic [ 23 25 ], ovarian, breast [ 26 , 27 ], and lung [ 28 ] cancer. Although there are some pieces of evidence about the role of HSULF-2 in cancer, its role in other noncommunicable diseases is partially known [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…HSPGs have a wide range of functions, including regulation of receptor tra cking, regulation of endocytosis and as a binding site for a wide range of ligands [26][27][28] . HSPGs wide range of functions are enabled by their HS chains 29 , which consist of long, unbranched negatively charged disaccharide repeats, varying in chain lengths and sulphation patterns 28,30 . Binding of proteins to the negatively charged HS require positively charged HS binding motifs 31,32 .…”
Section: Introductionmentioning
confidence: 99%